THE REPRESENTATION OF MEXICAN CULTURE IN DISNEY PIXAR’S MOVIE ENTITLED “COCO” - Istiwarni Diah; Siti Anisa; Budiarto Budiarto (STIBA IEC JAKARTA, 2021)
The aims of this research are (1) to find out the meaning of the day of the dead holiday (Día de Los Muertos) based on the movie; (2) to elaborate on the importance of the day of the dead holiday (Día de Los Muertos); and (3) to find out how to deal with a family conflict during the day of the dead holiday (Día de Los Muertos). This study uses a qualitative approach to address research problems as it enables the researcher to perform in-depth studies of a specific phenomenon. The findings or this research are (1) The meaning of the day of the dead holiday (Día de Los Muertos) based on Coco has some indicators such as symbols, heroes, and ritual (2) How the main character deals with his family conflict is that (a) The conflict which comes from the family culture is making the main character to become a rebel. Conflict is highly present in families; however, in general, the presence of conflict is not problematic by itself. (b) parents are making decisions about what they consider is best for all family members.